Foreign exchange interventions through currency swaps in Brazil : an empirical study of the effects on the spot exchange rate - Camargo, Luísa do Amaral (2019)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade, Departamento de Economia, Programa de Pós-Graduação em Ciências Econômicas, 2019.